Nature play in early childhood education: A systematic review and meta ethnography of qualitative research - Prins, Jannette; van der Wilt, Femke; van der Veen, Chiel; Hovinga, Dieuwke (Frontiers in Psychology, 2022)
Play in nature-based environments in childhood education has positive benefits for child development. Although previous reviews showed the benefits of play in nature-based environments for child development they did not attempt to understand how and why nature-based environments contribute to play quality. This review aims to explore the value of play in nature-based environments compared to non-nature-based environments for developmental outcomes of young children (2-8 year). We searched for studies that investigated the relation between play and nature-based environments on the databases PsycINFO, ERIC and Web of Science. Inclusion/exlusion criteria were: (1) the study focused on play in/on a nature based environment, (2) the study included participants between the age of 2-8 years, (3) it was an empirical study, (4) the study was conducted in the context of early childhood education (ECE), and (5) the study included participants without special needs or disabilities. Using these criteria we selected 28 qualitative studies with an overall sample size of N = 998 children aged 2-8 years. The studies were synthesized using an adaptation of Noblit and Hare’s meta-ethnographic approach. Three overarching themes were found: (1) the aspects of play quality that are related to nature-based environments, (2) the aspects of nature-based environments that support play, and (3) the aspects of teacher-child interactions that contribute to nature play quality. The meta themes resonate with play theories and theories of the restorative value of nature. We draw on the qualitative data to refine and extend these theories, and to come up with a definition of the concept ‘nature play’. This systematic review also sets a base for future research on play interventions in nature-based environments. We argue that (1) research will benefit from thoroughly conceptualizing the role of play in the development of young children, (2) using the affordances theory research will benefit from moving beyond the individual play actions as a unit of analysis, and (3) from an educational perspective it’s important to shift the focus of nature play to its benefits for children’s cognitive development.